Identification and Characterization of an Antennae-Specific Glutathione S-Transferase From the Indian Meal Moth - Liu, Hongmin; Tang, Yin; Wang, Qinying; Shi, Hongzhong; Yin, Jian; Li, Chengjun (Frontiers in Physiology, 2021)
Insect glutathione-S-transferases (GSTs) play essential roles in metabolizing endogenous and exogenous compounds. GSTs that are uniquely expressed in antennae are assumed to function as scavengers of pheromones and host volatiles in the odorant detection system. Based on this assumption, antennae-specific GSTs have been identified and functionally characterized in increasing number of insect species. In the present study, 17 putative GSTs were identified from the antennal transcriptomic dataset of the Indian meal moth, Plodia interpunctella, a severe stored-grain pest worldwide. Among the GSTs, only PiGSTd1 is antennae-specific according to both FPKM and quantitative real-time PCR (qRT-PCR) analysis. Sequence analysis revealed that PiGSTd1 has similar identity as many delta GSTs from other moths. Enzyme kinetic assays using 1-chloro-2,4-dinitrobenzene (CDNB) as substrates showed that the recombinant PiGSTd1 gave a Km of 0.2292±0.01805 mM and a Vmax of 14.02±0.2545 μmol•mg-1•min-1 under the optimal catalytic conditions (35 °C and pH=7.5). Further analysis revealed that the recombinant PiGSTd1 could efficiently degrade the sex pheromone component Z9-12:Ac (75.63±5.52%), as well as aldehyde volatiles, including hexanal (89.10±2.21%), heptanal (63.19±5.36%), (E)-2-octenal (73.58±3.92%), (E)-2-nonenal (75.81±1.90%), and (E)-2-decenal (61.13±5.24%). Taken together, our findings suggest that PiGSTd1 may play essential roles in degrading and inactivating a variety of odorants, especially sex pheromones and host volatiles of P. interpunctella.